HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT SELF ESTEEM (HARGA DIRI) PADA PENDERITA STROKE DI RUMAH SAKIT UMUM ROYAL PRIMA MEDAN 2019 - Zai, Yusmawarnita; Bu?ulolo, Kandrinus; Fajariani, Novy; Hulu, Yasozatulo; Gulo, Ruslan Efendi; Nurhayati, Eva Latifah (Jurnal Riset Hesti Medan, 2019)
Stroke is a condition where a part of the brain is suddenly disturbed which is caused by a lack of blood supply, which causes an inhibition of metabolic processes. As a result of a stroke affects the psychological function of the patient, so the patient feels his level of self-esteem decreases or is low. The role and support of families play an important role in the rehabilitation process to provide health services for stroke patients. The aim is to find out the relationship of family support with the level of self esteem (self-esteem) in stroke patients at the Royal Prima Medan Hospital in 2019. The design used a "cross sectional study" approach with a population of 2,690 people. Samples were stroke patients at RSU Royal Prima medan, as many as 25 respondents using accidental sampling techniques and questionnaires as research instruments. The test used is the chi-square test. The results of the study Based on the chi-square test found p value (<0.05) statistically shows that there is a relationship between family support and the level of self esteem (self-esteem) in stroke patients specifically there is a relationship between informational support (p-value = 0.009), assessment support (p-value = 0.003), Instrumental support is obtained (p-value = 0.009), Emotional support (p-value = 0.004) with the level of self esteem (self-esteem) in stroke patients. This research shows that good family support will positively impact the level of self esteem (self-esteem) in stroke patients.